2007
DOI: 10.1042/bst0350225
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinases and regulation of embryonic stem cell fate

Abstract: ES (embryonic stem) cell lines are derived from the epiblast of pre-implantation embryos and like the inner cell mass cells from which they are derived exhibit the remarkable property of pluripotency, namely the ability to differentiate into all cell lineages comprising the adult organism. ES cells and their differentiated progeny offer tremendous potential to regenerative medicine, particularly as cellular therapies for the treatment of a wide variety of chronic disorders, such as Type 1 diabetes, Parkinson's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
4
19
0
Order By: Relevance
“…These findings are consistent with previous reports showing increased Akt activity in trastuzumab-resistant cell lines (Tanner et al, 2004;Kucab et al, 2005) and suggest that the PI3-K/ Akt pathway is important in mediating the effects of HER2 signaling. It is also consistent with recent reports suggesting a role for Akt signaling in stem cell selfrenewal (Welham et al, 2007) and in mediating treatment resistance (Ma et al, 2007;Saal et al, 2007). Most recently, Berns et al (2007) identified the PI3K pathway as a major determinant of trastuzumab resistance in human breast tumors using a functional genomic approach.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with previous reports showing increased Akt activity in trastuzumab-resistant cell lines (Tanner et al, 2004;Kucab et al, 2005) and suggest that the PI3-K/ Akt pathway is important in mediating the effects of HER2 signaling. It is also consistent with recent reports suggesting a role for Akt signaling in stem cell selfrenewal (Welham et al, 2007) and in mediating treatment resistance (Ma et al, 2007;Saal et al, 2007). Most recently, Berns et al (2007) identified the PI3K pathway as a major determinant of trastuzumab resistance in human breast tumors using a functional genomic approach.…”
Section: Discussionsupporting
confidence: 89%
“…3). The PI3K /AKT signaling cascade is known to be responsive to LIF and has been previously shown to trigger the expression of Nanog and to facilitate efficient proliferation and survival of murine ESC [24]. Based on these observations, we hypothesize that LIF is involved in maintenance of self renewal in porcine cells.…”
Section: Discussionmentioning
confidence: 80%
“…Due to its essential role in cell survival, the PI3K/Akt pathway and inositol phosphatases that regulate it are proposed to play a role in stem cell self-renewal, maintenance, and differentiation. This includes several types of stem cells, including pluripotent stem cells, [31,[62][63][64][65] HSC, [20,22,[66][67][68] neural stem cells [69][70][71][72][73][74], and epithelial stem cells [75]. A recurring theme in several stem cell types is for the PI3K/Akt pathway to inactivate GSK3b thus promoting activation and nuclear translocation of b-catenin [76,77].…”
Section: Discussionmentioning
confidence: 99%